BRCA1 and BRCA2 mRNA-expression prove to be of clinical impact in ovarian cancer. Issue 6 (11th September 2018) - Tsibulak, Irina; Wieser, Verena; Degasper, Christine; Shivalingaiah, Giridhar; Wenzel, Sören; Sprung, Susanne; Lax, Sigurd; Marth, Christian; Fiegl, Heidelinde; Zeimet, Alain
Abstract Background Mutations inBRCA1 andBRCA2 are associated with better survival in ovarian cancer (OC) patients due to a better response to platinum-based chemotherapy. However, the impact of theBRCA1/2 mRNA-expression is not well characterized in OC. Patients and methods We investigatedBRCA1/2 mRNA-expression in 12 non-neoplastic fallopian tubes and 201 epithelial OCs in relation to their clinical characteristics. Results We found higherBRCA1/2 mRNA-expression in OCs compared to controls (P  = 0.011, P  < 0.001, respectively).BRCA1 mutated OCs exhibited lowerBRCA1 (P  = 0.014) but higherBRCA2 mRNA-expression (P  = 0.001). LowBRCA1 -expression was associated with favorable overall survival (OS) (P  = 0.012) and lowBRCA2 -expression with better progression-free survival (PFS) and OS (P  = 0.004, P  = 0.001, respectively). A subgroup-analysis showed that this effect was confined only to theBRCA1- wildtype cancers. Cox-regression confirmed the prognostic significance ofBRCA1 -expression for OS (P  = 0.028). Independency of the prognostic value ofBRCA2 -expression for PFS (P  = 0.045) and OS (P  = 0.015) was restricted to high-grade serous OCs. Fully platinum-sensitivity was characterized by lowerBRCA1/2 mRNA-expression inBRCA1 -wildtype cancers in comparison to platinum-refractory OC. Conclusion Our findings may reflect higher platinum-sensitivity due to reduced capacity of DNA damage repair in tissues with lowBRCA1/2 -expression. In this context, especially inBRCA -wildtype cancers both parameters could also be potential predictors for PARP-sensitivity.